Intersectional pedagogy : Complicating identity and social justice - Case, Kim A. (Routledge, 2017)
Intersectional Pedagogy explores best practices for effective teaching and learning about intersections of identity as informed by intersectional theory. Formatted in three easy-to-follow sections, this collection explores the pedagogy of intersectionality to address lived experiences that result from privileged and oppressed identities. After an initial overview of intersectional foundations and theory, the collection offers classroom strategies and approaches for teaching and learning about intersectionality and social justice. With contributions from scholars in education, psychology, sociology and women’s studies, Intersectional Pedagogy include a range of disciplinary perspectives and evidence-based pedagogy.
Keywords: approches et analyses; discipline; formations; féminisme décolonial; identités; intersectionnalité; justice sociale; outils; ouvrages de références; psychologie; pédagogie; ressource en ligne; sciences de l'éducation; sciences humaines; sociologie; thématiques; études de genres

Questionnements féministes et méthodologie de la recherche - Ollivier, Michèle; Tremblay, Manon (L'Harmattan, 2000)
La recherche féministe repose-t-elle sur une éthique de la recherche qui lui est propre, Est-elle mieux servi par les méthodes qualitatives que quantitatives ? Comment arrive-t-elle à concilier engagement politique et effort d'élaboration d'un discours vrai sur le monde ? Cet ouvrage présente quelques éléments essentiels de la réflexion féministe actuelle sur la méthodologie de la recherche en sciences humaines et sociales.
Keywords: approches et analyses; discipline; discours; fem1000; justice sociale; méthodologie; point de vue situé; premier cycle; pédagogie; sciences humaines; sciences sociales; thématiques; épistémologie